2021
DOI: 10.3390/molecules26216427
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metallic Nanoparticles on In Vitro Culture, Phenolic Profile and Biological Activity of Two Mediterranean Lamiaceae Species: Lavandula viridis L’Hér and Thymus lotocephalus G. López and R. Morales

Abstract: Nanoparticles (NPs) recently emerged as new chemical elicitors acting as signaling agents affecting several processes in plant metabolism. The aim of this work was to investigate the impact of the addition of copper oxide (CuO), zinc oxide (ZnO) and iron oxide (Fe3O4) NPs (<100 nm) at different concentrations (1, 5 and 10 mg/L) to the culture media on several morphological, physiological and -biochemical parameters of in vitro shoot cultures of Lavandula viridis L’Hér and Thymus lotocephalus G. López and R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(111 reference statements)
3
7
0
Order By: Relevance
“…Salvianolic acid F and sagerinic acid, although being identified for the first time in T. lotocephalus , were detected in other Thymus species ( T. zygis , T. pulegioides , T. fragrantissimus , and T. herba-barona ) [ 73 ]. As reported in previous studies with this species [ 6 , 15 , 17 ], rosmarinic acid was the major biocompound identified in the extracts (with a range of 12.5 g/kg in 7% PEG + MeJA to 58.2 g/kg in MeJA) ( Table 4 ). Rosmarinic acid has been demonstrated to have important biological properties, such as antioxidant, anti-inflammatory, antitumor, neuroprotective, and antimicrobial [ 74 , 75 ].…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…Salvianolic acid F and sagerinic acid, although being identified for the first time in T. lotocephalus , were detected in other Thymus species ( T. zygis , T. pulegioides , T. fragrantissimus , and T. herba-barona ) [ 73 ]. As reported in previous studies with this species [ 6 , 15 , 17 ], rosmarinic acid was the major biocompound identified in the extracts (with a range of 12.5 g/kg in 7% PEG + MeJA to 58.2 g/kg in MeJA) ( Table 4 ). Rosmarinic acid has been demonstrated to have important biological properties, such as antioxidant, anti-inflammatory, antitumor, neuroprotective, and antimicrobial [ 74 , 75 ].…”
Section: Resultssupporting
confidence: 72%
“…Moreover, SA treatments showed a positive effect in decreasing H 2 O 2 contents in I. walleriana under 1–4% PEG [ 51 ]. Excessive oxidative stress was also observed in other species subjected to different metal oxide NPs [ 9 , 17 , 58 , 59 ], which denotes the ROS effects induced by metals binding with proteins presenting SH bonds, which are found in plants.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations